Naples As Seen by Musicians: Intus Et Extra Cultura - Anfilova, Svitlana; Mykhailova, Olga (Journal of History Culture and Art Research, 2020)
The influence of Neapolitan culture on the work of G. Donizetti and F. Poulenc is the main issue and purpose of this paper. Peculiarities of the southern region of the Apennine Peninsula, distinguished by the beauty and poetry of nature, mild climate, richness of the folk song tradition that arose at the crossroads of various ethnic groups and languages, inspired the creative imagination of artists, musicians, and writers from different countries. The artistic heritage contains many examples of works dedicated to Italy and Naples, in particular. In contrast to the processes of mixing heterogeneous elements and continuous renewal, universalism remains a permanent feature of Italian self-identity. Having been formed in antiquity, it was actualized in the era of humanism in a number of creative projects. One of them is the spread of the essentially regional genre of villanella (or Canzone alla napolitana) throughout the entire European music area in the 16th century. The cycle "Nuits d’été à Pausillipe" by G. Donizetti becomes a kind of "response" to the processes of the past, demonstrating the sustainability of the Neapolitan song traditions in view of romantic vocal music and romanza genre. The composer’s deep comprehension of the features of national melos and character, with its characteristic poetry of experiencing nature and emotionality, determined the psychological mood of the composition. The hymnal praise of love and joys of life, the exaltation of the lyrical expression testify to the high degree of G. Donizetti’s immersion into the atmosphere of the city, which became his second small homeland. A different view of Naples appears in the piano suite "Napoli" by F. Poulenc. It is remarkable for the picturesque language and the immediacy of emotional expression, determined by deep interpenetration of the Italian and French cultures. The position of an onlooker is seen in composer’s praise of natural beauties of the city, liveliness and energy of its population, theatricality of events. The study makes it clear that the differences in the individual perception of Naples by G. Donizetti and F. Poulenc, who represent two types of Neapolitan images retranslation in music, are predetermined. The involvement of G. Donizetti tradition, acquired at the genetic level, is expressed in the choice of vocal type of expression, a special sense of musical and verbal intonation. F. Poulenc, representing a different national culture, focuses on the external representativeness of Neapolitan life, capturing it in a series of instrumental sketches.